DEVELOPMENT OF INTERACTIVE PHYSICS MODULES BASED ON AGRICULTURAL SYSTEMS TO IMPROVE STUDENTS’ LEARNING OUTCOMES - Ahmad, Desi Widyaningsih; Jasruddin, Jasruddin; Saman, Abdul (DAS CONFERENCE INTERNATIONAL SERIES, 2025)
This research aims to develop an interactive physics learning module based on agricultural systems in Polewali Mandar Regency. This module is designed to enhance students’ understanding of physics concepts applied in real-world contexts, particularly in the agricultural sector, which is the primary sector in the region. The interactive approach used aims to make students more active in the learning process by utilizing technology to enrich teaching materials and increase student engagement. The development method applied uses the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), which includes needs analysis, design of agriculture-based content, development of interactive materials, implementation in teaching, and evaluation of the module’s effectiveness. The research results show that the use of this module can significantly improve students’ learning outcomes. The improvement in learning outcomes is measured through pre- and post-test assessments, as well as observations of student engagement during the learning process. Students demonstrated a better understanding of physics concepts relevant to their lives, as well as improved skills in applying physics knowledge in the context of agriculture. Therefore, this module is expected to be an innovation in improving the quality of physics education in Polewali Mandar Regency, particularly in applying physics knowledge to local agricultural system.